THE SECOND YEAR SENIOR HIGH SCHOOL STUDENTS' GRAMMATICAL DIFFICULTIES IN PRESENTING SPOKEN EXPOSITION TEXT - ANISA WAHYUNI; RATMANIDA RATMANIDA; AN FAUZIA ROZANI SYAFEI (Universitas Negeri Padang, 2018)
This research aimed to describe students difficulties in presenting spoken exposition text, limited to the use of simple present tense. This research was a descriptive research, conducted in May-June 2017 at MAN 2 Padang. The population was Grade XI of Science program students of MAN 2 Padang. The sample was 38 students chosen by using stratified random sampling method. The research data was the clauses with grammatical mistakes found in the transcript of students speaking, obtained by a speaking test. The result of the research showed that the most frequent difficulties of verbal clauses using simple present tense were subject-verb agreement (51%) and the use of auxiliary verb (18%). The most frequent difficulties of nominal clauses using simple present tense were no verb (71%) and no subject (13%).